Behavioral and quality-of-life outcomes in different service models for methadone maintenance treatment in Vietnam - Nguyen, Hoang Long (BioMed Central, 2016)
Background:Integrating HIV/AIDS and methadone maintenance treatment (MMT) services with existing health care delivery system is critical in sustaining efforts to fight HIV/AIDS in large injection-driven epidemics. However, efficiency of different integrative service models is unknown. This study assessed behavioral and health-related quality-of-life (HRQOL) outcomes of MMT in four service delivery models and explored factors associated with these outcomes of interest. Methods:A cross-sectional survey was conducted in two HIV epicenters in Vietnam: Hanoi and Nam Dinh Province. All patients in five selected MMT clinics were invited to participate, and 1016 were interviewed (80–90 % response rate). Results:Respondents had a mean age of 35.8, taken MMT for average 16.5 months and 3.3 % on MMT for 36–60 months. The MMT integrated with rural district health center (DHC) has the highest prevalence of concurrent drug use (11.3 %). The percentage of condom use (last sexual intercourse) with primary and casual partners was lowest in the MMT at urban DHCs. Patients at the rural DHC reported very high proportions of pain/discomfort (37.8 %), anxiety/depression (43.1 %), and mobility (13.3 %). In regression models, poorer HRQOL outcomes were found in MMT models in the rural areas or without general health care, and among those patients who were HIV positive, reported concurrent drug use, and had higher numbers of previous drug rehabilitation episodes. Mobility and anxiety/ depression are factors that increased the likelihood of concurrent drug use among MMT patients. Conclusions:Outcomes of MMT were diverse across different integrative service models. Policies on rapid expansion of the MMT program in Vietnam should also emphasize on the integration with comprehensive health care services including psychological supports for patients